A primer on green finance: From wishful thinking to marginal impact - Jan Pieter Krahnen; Jörg Rocholl; Marcel Thum (Leibniz Institute for Financial Research SAFE, 2021)
We raise some critical points against a naïve interpretation of "green finance" products and strategies. These critical insights are the background against which we take a closer look at instruments and policies that might allow green finance to become more impactful. In particular, we focus on the role of a taxonomy and investor activism. We also describe the interaction of government policies with green finance practice - an aspect, which has been mostly neglected in policy debates but needs to be taken into account. Finally, the special case of green government bonds is discussed.
Keywords: 330; Green Finance; Climate Change; Sustainability; Taxonomy; ESG